Reverse strategy to locally advanced breast implant-associated anaplastic large cell lymphoma: A case report - Cappelli, Sonia; Marchesi, Francesco; Clementi, Marco; Perracchio, Letizia; Palombi, Francesca; Pelle, Fabio; Botti, Claudio; Costantini, Maurizio (Frontiers in Oncology, 2023)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare T-cell lymphoma associated with textured breast implants. The most common presentation is a periprosthetic seroma that occurs at least 1 year after an aesthetic or reconstructive implantation, and in these cases, the surgical treatment seems to be successful. More rarely, BIA-ALCL presents with locally advanced mass-formed disease and a related regional lymph node involvement. In all these cases with worse prognosis, a multidisciplinary approach is required, including adjuvant chemotherapy, radiation therapy, and surgery. We present a clinical case of a 49-year-old woman who developed on the left side of the breast a mass-formed stage 3 BIA-ALCL 15 years after a bilateral breast augmentation with textured silicone implant. Our multidisciplinary team (MDT) scheduled the patient for a “reverse-strategy” sequential approach consisting of induction chemotherapy, hematopoietic stem cell mobilization, and harvest followed by autologous stem cell transplant (ASCT). After 100 days from the stem cell transplant, the patient showed a complete pathologic response and was a candidate for radical surgery. She underwent removal of both implants with total en bloc capsulectomy. On the left site, the periprosthetic mass was also en bloc removed. We did not perform any axillary dissection. Our surgical and hemato-oncological teams followed the patient every 3 months, and no local or systemic recurrences were observed 24 months after surgery. This case report has demonstrated the effectiveness of neoadjuvant chemotherapy as part of a “reverse strategy” in selected cases of advanced-stage BIA-ALCL in which it was not possible to perform an immediate radical surgery. Furthermore, in our case, the de-escalation strategy adopted permitted a less demolitic surgery with good functional and aesthetic results.